Study of adsorption of the SARS-CoV-2 virus spike protein by vibrational spectroscopy using terahertz metamaterials. (January 2022) - Konnikova, M R; Cherkasova, O P; Geints, T A; Dizer, E S; Man'kova, A A; Vasil'evskii, I S; Butylin, A A; Kistenev, Yu V; Tuchin, V V; Shkurinov, A P
Abstract: Adhesion of the spike protein of the SARS-CoV-2 virus is studied by vibrational spectroscopy using terahertz metamaterials. The features of metastructure absorption upon the deposition of histidine, albumin, and the receptor-binding domain of the spike protein films are investigated. An original technique for quantitative assessment of the efficiency of virus adhesion on the metamaterial surfaces are proposed and experimentally tested.